Level of Students’ Environmental Literacy based on Components of Knowledge, Attitude, and Behaviour - Yahya Hanafi; Nani Aprilia; Arief Abdillah Nurusman (Bioeducation Journal, 2023)
Environmental problems include pollution, loss of habitat, climate change, and decreased biodiversity related to human behavior. People who have environmental literacy will behave more responsibly towards their environment. An alternative solution that can be done is to build community environmental literacy through education. This study aims to analyze the level of environmental literacy of students based on the components of knowledge, attitudes, behavior. This type of research is quantitative with a survey method. Research respondents are students from 23 provinces in Indonesia who are currently studying at the Biology Education Study Program, Ahmad Dahlan University, with 93 respondents. The data collection technique uses a questionnaire, and the instrument uses an environmental literacy questionnaire (knowledge, attitudes, and behavior components). Validation of the instrument using exploratory factor analysis and reliability using Cronbach's Alpha. The data analysis technique used is descriptive quantitative. The level of environmental literacy in the knowledge component of 69.55% (high criteria), 1.08% (moderate criteria), and 29.37% (low criteria). Components of student attitudes obtained 62.37% in the excellent; 13.04% neutral; 24.59% in the poor. The behavioral component 52.93% gave an occasional response; 37.28% always; and 9.80% never. Students' level of environmental literacy on the components of knowledge and attitudes is not in line with the behavior shown. Knowledge about the environment and attitudes care for the environment owned by students have not been fully expressed in the behavior that is responsible for the environment. Students have not fully implemented the knowledge and attitude components into the behavioral components.